2021
DOI: 10.3389/fpsyg.2021.764715
|View full text |Cite
|
Sign up to set email alerts
|

“Stay at Home”: The Effects of the COVID-19 Lockdown on Household Food Waste in Colombia

Abstract: Household food waste represents one of the main challenges for sustainable development as this directly affects the economy of food consumers, the loss of natural resources and generates additional greenhouse gas emissions. The COVID-19 pandemic and its mitigation strategies caused one of the most serious economic crises in recent decades and could become the worst economic crisis that Latin America has had in its history. The objective of this study is to analyze changes in food waste behavior during the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Because restaurants and coffee shops are closed, most meals are prepared and enjoyed at home, resulting in fewer leftovers being thrown away. Different studies have shown a similar decrease in food wastage during the pandemic in countries such as Italy ( Amicarelli et al., 2021a , Amicarelli et al., 2021b ; Pappalardo et al., 2020 ; Vittuari et al., 2021 ), Lebanon ( Ben Hassen et al., 2021c ), Colombia ( Mejia et al., 2021 ), Qatar ( Ben Hassen et al., 2020 ), Bosnia and Herzegovina ( Ben Hassen et al., 2021d ), Serbia ( Berjan et al., 2021 ) as well as in the European Union ( Bel and Marengo, 2021 ). In general, reducing food wastage requires improving purchase planning, knowledge of labels, and food storage and cooking skills ( Vásquez Neyra et al., 2022 ).…”
Section: Discussionmentioning
confidence: 74%
“…Because restaurants and coffee shops are closed, most meals are prepared and enjoyed at home, resulting in fewer leftovers being thrown away. Different studies have shown a similar decrease in food wastage during the pandemic in countries such as Italy ( Amicarelli et al., 2021a , Amicarelli et al., 2021b ; Pappalardo et al., 2020 ; Vittuari et al., 2021 ), Lebanon ( Ben Hassen et al., 2021c ), Colombia ( Mejia et al., 2021 ), Qatar ( Ben Hassen et al., 2020 ), Bosnia and Herzegovina ( Ben Hassen et al., 2021d ), Serbia ( Berjan et al., 2021 ) as well as in the European Union ( Bel and Marengo, 2021 ). In general, reducing food wastage requires improving purchase planning, knowledge of labels, and food storage and cooking skills ( Vásquez Neyra et al., 2022 ).…”
Section: Discussionmentioning
confidence: 74%
“…Within the literature review that relates the effects of COVID-19 with food consumption, two main sources of research were found. First, studies focused on the supply side, i.e., on limitations in supply [e.g., (32-34)], and second, studies focused on the demand side, i.e., on changes in demand and consumer preferences [e.g., (25,29,30,(35)(36)(37)]. Analyses of the combined effects on supply and demand are rather scarce and occasionally provided rather by non-governmental organizations [e.g., (2)].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review shows that most studies on the effects of COVID-19 on food markets were carried out in the regions or countries mostly affected by the pandemic, namely Asia [e.g., ( 35 )], Europe [e.g., ( 27 – 29 , 37 )], the United States [e.g., ( 28 , 34 , 38 )]; and Latin America [e.g., ( 29 , 30 , 36 )]. Regarding research techniques, it is found that the studies are mostly focused on the use of surveys or information collected with representative samples during the most critical months of the pandemic, which provides information on the population interviewed and the reasons for making their decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Many participants reported that their thoughts toward food waste have changed as a result of the economic recession that the country is experiencing where they think more about ways to use leftovers and plan their shopping lists better in order to avoid spending money on items they do not really need. This proves that populations experiencing financial and economical hardships do in fact shift their behaviors towards taking measures to avoid suffering the negative consequences (Mejia et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The present study examined how household characteristics and food-related behaviors affected food waste generation in light of a deteriorating economic crisis and a pandemic. According to Mejia et al (2021),…”
Section: Discussionmentioning
confidence: 99%